Innovative screening methods to reduce the misdiagnosis of Lyme disease: Public health and global implications - Diala Ra’Ed Kamal Kakish; Jehad Feras AlSamhori; Mohammed Al-Sawalha; Wafaa Shehada; Asham Al Salkhadi; D. Prashasti; Ibrahim Almaliti; Mohammad Al-Zuriqat; Qais Akasheh; Abdulqadir J. Nashwan (The Microbe)
Lyme disease remains a persistent global health concern, complicated by diagnostic delays and high rates of misdiagnosis, particularly in early-stage presentations and underserved populations. Conventional two-tier serological testing is hampered by limited sensitivity, antigenic cross-reactivity, and poor performance in acute disease. Recent advancements in diagnostic innovation, including Modified Two-Tier Testing (MTTT), synthetic peptide-based platforms, bacteriophage-targeted PCR, and MENSA (Medium Enriched for Newly Synthesized Antibodies), offer enhanced sensitivity, specificity, and real-time immune profiling. In parallel, developments in therapeutic and preventive strategies, such as cyclic antimicrobial peptides and microbiota-targeted vaccines, underscore a growing emphasis on translational approaches to persistent infection and vector control. This review provides a novel synthesis of diagnostic and therapeutic advances in Lyme disease, uniquely bridging molecular tools, public health disparities, and precision medicine.